Diffusive vertical heat flux in the Canada Basin of the Arctic Ocean inferred from moored instruments. Issue 1 (22nd January 2014) - Lique, Camille; Guthrie, John D.; Steele, Michael; Proshutinsky, Andrey; Morison, James H.; Krishfield, Richard
<x xml:space="preserve">Abstract</x> [1] Observational studies have shown that an unprecedented warm anomaly has recently affected the temperature of the Atlantic Water (AW) layer lying at intermediate depth in the Arctic Ocean. Using observations from four profiling moorings, deployed in the interior of the Canada Basin between 2003 and 2011, the upward diffusive vertical heat flux from this layer is quantified. Vertical diffusivity is first estimated from a fine‐scale parameterization method based on CTD and velocity profiles. Resulting diffusive vertical heat fluxes from the AW are in the range 0.1–0.2 W m−2 on average. Although large over the period considered, the variations of the AW temperature maximum yields small variations for the temperature gradient and thus the vertical diffusive heat flux. In most areas, variations in upward diffusive vertical heat flux from the AW have only a limited effect on temperature variations of the overlying layer. However, the presence of eddies might be an effective mechanism to enhance vertical heat transfer, although the small number of eddies sampled by the moorings suggest that this mechanism remains limited and intermittent in space and time. Finally, our results suggest that computing diffusive vertical heat flux with a constant vertical diffusivity of ∼2 × 10−6 m2 s−1 provides a reasonable estimate of the upward diffusive heat transfer from the AW layer, although this approximation breaks down in the presence of eddies.